MO565M2 MACROPHAGES REGULATE MOUSE AORTIC SMOOTH MUSCLE CELL CALCIFICATION BY TRANSMITTING SENESCENCE INFORMATION. (29th May 2021) - Fang, Yaping; Zhu, Xiaodong; Zhao, Yu; Zhang, Xiao liang
Abstract: Background and Aims: Vascular calcification is highly prevalent in chronic kidney disease (CKD)with high morbidity and mortality. Complex pathological mechanisms are involved in the development of vascular calcification, including aging. Previous work have indicated that M2-macrophage promote mouse aortic smooth muscle cells (MAoSMCs) calcification. The present study aimed to understand the contribution of M2-macrophage to MAoSMCs calcification by focusing on the mechanisms underlying the transmitting senescence information Method: The expression of IFITM3 and P16, marker of aging, in aging macrophages were confimed by RT-qPCR, western blotting and immunofluorescence staining. Then, the MAoSMCs were co-cultured with the supernatant of M2 macrophages. The expression of IFITM3 and P16 in MAoSMCs also were detected. Alizarin red staining and calcium content assay were used to analyse MAoSMCs calcification. We modulated the expression of IFITM3 using siRNAs to study M2-macrophages function in regulating MAoSMCs calcification.We detected the expression of IFITM3 and P16 in co-cultivate MAoSMCs and validate intracellular calcium contents by calcium test kit. Results: In the present study, we observed a significant increase in the expression of IFITM3 and P16 expression in M2 macrophages.Compared with M0 and M1 macrophages, the expression of IFITM3 and P16 at lowlevel. Alizarin red staining and calcium content assay revealed that M2 macrophage-mediated IFITM3 and P16 overexpression led to an apparent VSMC calcification in the presence of M2 macrophages medium.By contrast, inhibition of IFITM3 by siRNAs significantly blocked calcification of VSMCs in vitro. Moreover, we found that aging macrophages that overexpressed of IFITM3 and P16 increased in rats with CKD. Furthermore, pharmacological inhibition of aging signal was shown to block IFITM3-induced VSMC calcification. These findings demonstrate for the first time that M2 macrophage-mediated IFITM3 contributes to vascular calcification through a mechanism involving transmitting Senescence signalling. Conclusion: Collectively, our present study demonstrated that the functional importance of M2 macrophage-IFITM3 dependent vascular calcification and provided a novel mechanistic insight to the macrophage senescence in CKD.